2019
DOI: 10.1186/s12957-019-1660-2
|View full text |Cite
|
Sign up to set email alerts
|

Intrapancreatic accessory spleen false positive to 68Ga-Dotatoc: case report and literature review

Abstract: Background Intrapancreatic accessory spleen (IPAS) is an uncommon finding of pancreatic mass. Differential diagnosis with pancreatic tumor, especially with non-functional neuroendocrine tumor (NF-NET), may be very hard and sometimes it entails unnecessary surgery. A combination of CT scan, MRI, and nuclear medicine can confirm the diagnosis of IPAS. 68-Ga-Dotatoc PET/CT is the gold standard in NET diagnosis and it can allow to distinguish between IPAS and NET. Case presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Literature documents many case reports of false positives on PET-CT NETSPOT due to ectopic splenic anomalies [12][13][14][15][16][17]. One case report with a literature review showed that 66.7% of patients with intrapancreatic accessory spleen ended up undergoing unnecessary pancreatic resections [13]. With advanced imaging techniques and early detection, fear of overtreatment of this benign incidental process exists [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Literature documents many case reports of false positives on PET-CT NETSPOT due to ectopic splenic anomalies [12][13][14][15][16][17]. One case report with a literature review showed that 66.7% of patients with intrapancreatic accessory spleen ended up undergoing unnecessary pancreatic resections [13]. With advanced imaging techniques and early detection, fear of overtreatment of this benign incidental process exists [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…68 Galabeled somatostatin analogs (DOTA-TOC, DOTA-TATE, DOTA-NOC) for Positron Emission Tomography/Computed Tomography (PET/CT) has emerged as a reliable imaging modality for well-differentiated neuroendocrine tumors [53][54][55]. However, since splenic tissue also demonstrates high uptake of somatostatin analogs, this modality does not enable the differentiation of IPS from PNETs [56,57]. Our clinical implementation of feMRI resulted in reliable distinction between IPS and PNETs.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually asymptomatic so that most of the cases are diagnosed incidentally, except for some cases with abdominal pain or idiopathic thrombocytopenic purpura after splenectomy [14]. It is 1-3 cm in size, well-delimited, homogenous, and hypervascular on CT and MRI [15,16]. Tumoral and neuroendocrine markers are usually negative in IPAS, but there has been a report with slightly elevated tumoral markers in the patient with IPAS [17].…”
Section: Discussionmentioning
confidence: 99%